Uncertainty and spillover effects across the euro area - Giovanni Angelini; Mauro Costantini; Joshy Z. Easaw (Cardiff University, Cardiff Business School, 2018)
This paper investigates how macroeconomic uncertainty shocks spillover over four Eurozone countries. It also evaluates their impact on real economic activity. The paper proposes a simple two-country model with a core and a periphery economy, where uncertainty shocks spread from one country to another, with potential feedback fromthe periphery economy to the core one. An empirical analysis is conducted using a Structural Vector Autoregressive (SVAR) model with two regimes: pre-crisis period and crisis period. The findings point to uncertainty spillovers among the Eurozone countries, with some feedback from periphery economies to the core economies during the financial crisis period. Further, there is a need to account for spillovers when studying the impact of uncertainty on real economic activity.
Keywords: C32; C50; E32; 330; Uncertainty; Euro Area; Spillover effects; Real Economic Activity